2019
DOI: 10.20886/jphka.2019.16.2.159-171
|View full text |Cite
|
Sign up to set email alerts
|

Kepadatan Kuskus Genus Phalanger Dan Identifikasi Tumbuhan Pakannya Di Pulau Obi

Abstract: Kontribusi penulis: MNT: mendesain ide penelitian, menyusun proposal, melaksanakan penelitian, menganalisis data, menyusun laporan penelitian dan menyusun artikel hasil penelitian; BLP dan R: mengumpulkan data lapangan; SH: menganalisis data dan menyusun artikel hasil peneltian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
1
2
1
Order By: Relevance
“…The cuscus population density in this study was lower than the other study on Obi Island, which found that the cuscus density of the phalanger genus on the island was 25 individuals/ha [22]. Another research on cuscus populations in the Arfak Mountains Nature Reserve, whinch also stated higher densities for the Northern common cuscus (P. orientalis), the ground cuscus (P. gymnotis) and the common spotted cuscus (S. maculatus), spesifically with a density value of 67 individuals/ha, 17 individuals/ha, and 11 individuals/ha [23].…”
Section: Cuscus Populationcontrasting
confidence: 90%
See 1 more Smart Citation
“…The cuscus population density in this study was lower than the other study on Obi Island, which found that the cuscus density of the phalanger genus on the island was 25 individuals/ha [22]. Another research on cuscus populations in the Arfak Mountains Nature Reserve, whinch also stated higher densities for the Northern common cuscus (P. orientalis), the ground cuscus (P. gymnotis) and the common spotted cuscus (S. maculatus), spesifically with a density value of 67 individuals/ha, 17 individuals/ha, and 11 individuals/ha [23].…”
Section: Cuscus Populationcontrasting
confidence: 90%
“…Several factors influence the presence of animals in a habitat. The presence of cuscus on Obi Island was influenced by the availability of food, predators, and habitat conditions [22].…”
Section: Cuscus Distribution Mapmentioning
confidence: 99%
“…Hence, food outside the forest area is likely to be exploited by the animals. This result is lower compared to the estimated population in Obi Island (Tamalene et al 2019) and Arfak Mountains Nature Reserve, which was relatively abundant (Sinery 2022).…”
Section: Palatability Of Organic Matter In Ration Combinationcontrasting
confidence: 61%
“…Salah satu fauna khas sebagai bentuk keanekaragaman tersebut adalah Kuskus. Kuskus adalah fauna marsupial dari Australia yang termasuk ke dalam keluarga Phalangeridae (Tamalene et al, 2019) dan tergolong sebagai fauna langka endemik dengan persebaran terbatas pada bagian timur Indonesia seperti Maluku, Sulawesi, Papua/Irian Jaya, Pulau Timor (Darenoh et al, 2019), Australia, serta Papua New Guinea (Kasi et al, 2019).…”
Section: Pendahuluanunclassified